برنامج دعم الشباب والتشغيل (paje) كآلية لدعم التنمية المحلية-ولاية بشار نموذجا للفترة (2017 الى 2021) - سعيدان, رشيد; قصابي, موسى (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الورقة البحثية الى ابراز أهمية التشغيل كاستراتيجية فعالة في تحقيق التنمية الاقتصادية والاجتماعية في الجزائر، وذلك من خلال الإجابة على التساؤل كيف ساهم برنامج دعم الشباب والتشغيل paje في تحقيق التنمية المحلية لولاية بشار. ومن أجل الاجابة على هذه الإشكالية انتهجنا المنهج الوصفي الاستقرائي بغية تحليل واقع مدى مساهمة هذا البرنامج في دعم الاستثمار المحلي وخلق مناصب عمل. وقد توصلت الدراسة الى أن البرنامج ساهم فعليا في عملية التنمية المحلية من خلال توسيع الأنشطة الاقتصادية للمنطقة وخلق مناصب عمل، كما أوصت الدراسة بضرورة زيادة فعاليات النسيج الجمعوي بإشراكه في مجال الشغل والابتكار. Abstract : This research paper aims to highlight the importance of employment as an effective strategy in achieving the economic and social development in Algeria, by answering the question how the Paje Youth Support and Employment Program has contributed in the inhance of the local development at Bashar’s state. In order to answer this problem, we adopted the descriptive and inductive approach to analyze the reality of how this program contributes in supporting local investment and creating jobs. The study concluded that the program actually contributed to the local development by expanding the economic activities of the region and creating jobs. Also recommended the need to increase the activities of associative activity by involving it in the field of employment and innovation.
Keywords: Keywords: employment, local development, Paje program, Bechar State. ; التشغيل، التنمية المحلية، برنامج Paje، ولاية بشار.